Analyse vibratoire par sous-structuration avec modèle non paramétrique d’incertitudes aléatoires non homogènes - Chebli, Hamid; Soize, Christian (European Journal of Computational Mechanics, 2002)
In linear vibration analysis, numerical predictions of complex structures modelled by the finite element method can be improved by taking into account the random uncertainties due to modelling and model errors. Usually, the parametric methods are used to take into account the uncertainties due to modelling errors. Recently, a nonparametric method has been introduced and allows the homogeneous random uncertainties due to modelling and model errors to be taken into account. In this paper, one presents an extension of this theory for the case of non-homogeneous random uncertainties by using the nonparametric approach and the Craig & Bampton dynamic substructuring. A numerical example is presented.